De l'[EMOCIÓ] a la [CONTRA VOLUNTAT]: el procés de gramaticalització de malgrat als segles XII-XVI. - MARTÍNEZ, CATERINA (Scripta)
The present study focuses on the process of grammaticalization of malgrat, from the paper as an original Noun Phrase expressing an [emotion] to the value of [against will] that it has reached as a Preposition Phrase. We pay special attention to the retraction experienced by malgrat just as from the 16th century. We examine the evolution of malgrat according with the proposals of Cognitive Linguistics and, specially, the Theory of Grammaticalization, and we combine them with the approaches of Discourse Analysis, Argumentation Theory and Pragmatics. The defense of the linguistic change rooted in the use, in accordance with the Theory of Intersubjectivity, helps us to review the sources and the values of malgrat in Catalan.